A flexible homoleptic pentadentate Cu(II) molecular catalyst for effective proton and water reduction. (10th September 2020) - Majee, Karunamay; Rai, Surabhi; Panda, Binata; Padhi, Sumanta Kumar
Abstract: A copper (II) based molecular catalyst [Cu(tpen)](PF6 )2 has been synthesized, and employed for the catalytic activity towards hydrogen evolution both in organic and aqueous media (where tpen = N, N, N′, N'-Tetrakis(2-pyridylmethyl)ethylenediamine). The acid-base equilibria of the complex in phosphate buffer suggest that the initial protonation occurs at the free N atom of the pyridine ring. The pKa value for the [Cu(tpenH)] 3+ ⇆ [Cu(tpen)] 2+ was found to be 4.6. The electrocatalytic activity of the [Cu(tpen)](PF6 )2 towards proton reduction in organic media was determined in presence of acetic acid as an external proton source. Controlled potential electrolysis was performed for the [Cu(tpen)](PF6 )2 complex in the presence of acetic acid with varying overpotential ranging from 555 mV to 955 mV vs. SCE for 2 h, and a Faradaic efficiency of 89 ± 5% was observed. Electrochemical proton reduction by the complex follows first-order dependency with respect to complex concentration, and it is second order with respect to the concentration of acetic acid. The ic /ip value for the [Cu(tpen)](PF6 )2 complex in the acid independent region was found to be 133 at a scan rate of 100 mV s −1 with observed rate constant (kobs ) of 3415 s −1 . The [Cu(tpen)](PF6 )2 complex also undergoes the electrochemical proton reduction in aqueous media to evolve hydrogen. The catalyst generates hydrogen from an aqueous medium at pH 7.0 in phosphate buffer. The plausible mechanisms for pH higher than the pKa value has been derived from the spectroscopic evidence and supported by DFT studies, wherein an EECC process is involved in the catalytic cycle (E = electrochemical; C = chemical). Graphical abstract: Image 1 Highlights: Complex [Cu(tpen)](PF6 )2 has been synthesized and characterized by single-crystal XRD. The complex is capable of generating hydrogen from acetic acid (AcOH). The complex generates hydrogen from water at pH 7.0 in phosphate buffer. The structural flexibility improves the catalytic activity. The complex follows EECC path for H2 evolution.